Dataset_PSMU_EI_gender. - Arrivillaga, Christiane; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (Universidad de Málaga, 2024)
The excessive usage of social networking sites might affect adolescents’ well-being. Recent studies have found significant associations between problematic social media use (PSMU) and psychological maladjustment. The present study aimed at analyzing gender differences in the percentages of high-risk PSMU and to investigate the relations with the emotional intelligence (EI) of adolescents. The sample was composed of 597 adolescents (58.8 % girls, 45.2 % boys) within the ages of 12 and 19. Participants completed self-report questionnaires of EI (WLEIS) and PSMU (BSMAS). Results indicate that girls had higher high-risk percentages of PSMU (17.7 %) than boys (13.4 %). Furthermore, boys had higher levels of self-emotion appraisal, regulation of emotions and global EI, while girls had higher levels of other-emotion appraisal. Nonetheless, when correlational analyses were divided by gender, only in girls there was a significant and negative association between PSMU and self-emotion appraisal, use of emotions, regulation of emotions and global EI. Results indicate that the higher risk of PSMU found in girls could be related to their lower levels of self-emotion appraisal, regulation of emotions and global EI. The findings highlight the importance of designing gender sensitive PSMU prevention strategies.
Keywords: Adolescentes - Psicología; Redes sociales en internet - Aspectos psicológicos; Adolescence; Problematic social media use; Emotional intelligence; Gender